Hormesis in Regulatory Risk Assessment - Science and Science Policy - George Gray (SAGE Publishing, 2011)
This brief commentary will argue that whether hormesis is considered in regulatory risk assessment is a matter less of science than of science policy. I will first discuss the distinction between science and science policy and their roles in regulatory risk assessment. Then I will focus on factors that influence science policy, especially as it relates to the conduct of risk assessments to inform regulatory decisions, with a focus on the U.S. Environmental Protection Agency (EPA). The key questions will then be how does hormesis interact with current concepts of science and science policy for risk assessment? Finally, I look ahead to factors that may increase, or decrease, the likelihood of hormesis being incorporated into regulatory risk assessment.